2016
DOI: 10.1097/meg.0000000000000688
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single-session transarterial chemoembolization combined with microwave ablation or radiofrequency ablation in the treatment of hepatocellular carcinoma: a randomized-controlled study

Abstract: Combined ablation with chemoembolization is superior in the treatment of nonresectable single masses larger than 4 cm. Transcatheter arterial chemoembolization and ablation can be performed safely and successfully during a single session, which has not been found to decrease the response rates to treatment. Combined treatment with MWA is more effective in terms of tumor response, and results in the same complication rate as with radiofrequency, but less than chemoembolization alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 32 publications
2
57
0
Order By: Relevance
“…The improvement is mainly attributed to the reduction of heat-sink effect due to the vascular outflow of the liver (17). Furthermore, a randomized-controlled study in 2016 found that TACE-MWA combination therapy was more effective than TACE-RFA combination therapy in unresectable single-lesion HCC patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…The improvement is mainly attributed to the reduction of heat-sink effect due to the vascular outflow of the liver (17). Furthermore, a randomized-controlled study in 2016 found that TACE-MWA combination therapy was more effective than TACE-RFA combination therapy in unresectable single-lesion HCC patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 represents different options for HCC therapeutic modalities used. Recently, results of studies for HCC treatment and prevention of complication have been reported [86][87][88][89]. Details about clinical trials in Egypt will be discussed in HCC research section.…”
Section: Treatment Approachmentioning
confidence: 99%
“…After a preliminary review, 418 papers were excluded because they were considered irrelevant studies, case reports, animal studies, comment letters, or reviews. Among 32 potentially relevant papers, we excluded five studies in which patients were treated with embolization combined with MWA or RFA [12][13][14][15][16] and another seven because of insufficient data [17][18][19][20][21][22][23]. Six studies were excluded because of duplicate data [24][25][26][27][28][29].…”
Section: Statistical Analysesmentioning
confidence: 99%